Utilization Of Digital Media In English As A Foreign Language (EFL) Classess At The Junior High School Level In The “Program Sekolah Penggerak” - Dheasari, Hafilda Aprillia; Ciptaningrum, Dyah Setyowati (STKIP Singkawang, 2024)
This study investigates the challenges and practices of teachers’ use of digital media in the “Program Sekolah Penggeak”. Through qualitative case study methodology, observation, semi-structured interviews and document analysis, this study investigates the implementation of digital media in English language learning in “school mover”. The findings highlight the importance of knowing what types of digital media can be used in the learning process, especially English, how teachers utilize digital media in the English language learning process, as well as the challenges and adjustments of strategies in using digital media. Recommendations include enhanced professional development to learn new technologies and digital skills and supportive school policies to navigate the barriers to implementing digital media utilization.